Dietary habits of newcomer children in Canada. Issue 17 (7th August 2019) - Lane, Ginny; Nisbet, Christine; Vatanparast, Hassan
Abstract: Objective: To explore the dietary habits, nutrient adequacies and dietary change experiences of immigrant and refugee children. Design: Mixed-methods cross-sectional design. Children completed three 24 h dietary recalls to determine nutrient inadequacies. Parents and service providers were interviewed to capture dietary practices. Setting: Healthy Immigrant Children study, Saskatchewan, Canada. Participants: Three hundred immigrant and refugee children aged 3–13 years and twenty-two parents who lived in Regina or Saskatoon for less than 5 years; twenty-four newcomer services providers. Results: Immigrant children had higher mean intakes of meat and alternatives, milk and alternatives, and whole grains; and consumed more vitamin B12, folate, Ca, vitamin D, Fe and Zn compared with refugee children. Refugee children were at higher risk of having inadequate intakes of folate (37 %) and Fe (18 %). Both immigrant and refugee children were at high risk of inadequate vitamin D (87 and 93 %, respectively) and Ca intakes (79 and 80 %), and a substantial portion were at risk for inadequate Zn intake (21 and 31 %). Participants mentioned challenges with maintaining a healthy traditional diet in the midst of a busy schedule, while responding to their children's demands for foods high in fat and sugar. Conclusions: Newcomer children are at risk for inadequate intakes of vitamin D, Ca and Zn, while refugee children are at additional risk for inadequate folate and Fe intakes. Newcomers to Canada may experience subtle or drastic changes in their food environment leading to dietary acculturation that includes increased consumption of foods high in sugar, salt and fat.